2014
DOI: 10.1007/s11274-014-1774-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the aroma of white wines by controlled Torulaspora delbrueckii cultures in association with Saccharomyces cerevisiae

Abstract: Although the positive role of non-Saccharomyces yeasts on the overall quality of wine is encouraging research into their oenological potential, current knowledge on the topic is still far from satisfactory. This work analyzes the contribution of starter cultures of Torulaspora delbrueckii, inoculated sequentially with Saccharomyces cerevisiae (multi-starter fermentation), on the fermentation and aromas of two different white style wines, i.e., dry and sweet wines. Chemical analysis of Soave and Chardonnay wine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
97
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 35 publications
22
97
1
Order By: Relevance
“…1). The duration of these co-inoculated fermentations is similar to that in other studies, which took between 12 and 24 days, but the single-inoculant group took much longer (24 vs. 32 days) (Azzolini et al, 2015;Belda et al, 2015). The zero-hour co-inoculations fermented at the same rate (slope of logarithmic growth phase) as the S. cerevisiae reference yeast.…”
Section: Small-scale Vinification: Chenin Blancsupporting
confidence: 81%
See 3 more Smart Citations
“…1). The duration of these co-inoculated fermentations is similar to that in other studies, which took between 12 and 24 days, but the single-inoculant group took much longer (24 vs. 32 days) (Azzolini et al, 2015;Belda et al, 2015). The zero-hour co-inoculations fermented at the same rate (slope of logarithmic growth phase) as the S. cerevisiae reference yeast.…”
Section: Small-scale Vinification: Chenin Blancsupporting
confidence: 81%
“…The alcohol levels were only lower where less sugar was consumed, showing that these T. delbrueckii isolates are not suitable as a means for lowering the alcohol content of the wine. This is in contrast to other published works where, T. delbrueckii vinifications produced between 0.14% and 0.47% lower alcohol levels than reference S. cerevisiae fermentations (Azzolini et al, 2015;Belda et al, 2015;Renault et al, 2015). Glycerol produced by the single-inoculant fermentations was found to be slightly higher than in the co-inoculated wines and the S. cerevisiae reference fermentation, which is similar to what has been observed in other trials (Jolly et al, 2003a;Belda et al, 2015).…”
Section: Small-scale Vinification: Chenin Blancsupporting
confidence: 53%
See 2 more Smart Citations
“…Several studies have reported on positive influences of non-Saccharomyces yeast species on wine quality, with evaluation of the specific involvement of selected strains [1][2][3]. In this context, there is an increasing interest in the practice of co-inoculation of grape juice with a Saccharomyces cerevisiae starter strain coupled with a selected culture of a non-Saccharomyces yeast.…”
Section: Introductionmentioning
confidence: 99%